(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Koneri R, Langoy MD, Nangoy MJ, Wakhid. 2024. Pollinator insects in the Mount Tumpa Forest Park, Manado, North Sulawesi, Indonesia. Biodiversitas 25: 2415-2426. This study aimed to analyze the diversity and distribution of pollinator insects in forest, forest edge, shrub, and agricultural land around the Mount Tumpa Forest Park, Manado, North Sulawesi, Indonesia, using the scan sampling method. Data analysis included species abundance, species dominance, richness index, diversity index, species evenness index, correlation between environmental factors, species diversity, and composition of pollinator insect species among habitats. Therefore, 17 families were reported, comprising 103 species and 3,665 individuals. The family with the highest number and most frequently encountered was Nymphalidae (25 species). Furthermore, the highest species richness and diversity indices were found in the forest edge habitat. Environmental factor analysis indicated that agricultural land habitat was characterized by high air temperature and low humidity. The species distribution found three patterns: clustered, regular, and random. The results showed that the forest edge habitat had the highest diversity due to complex vegetation structure and environmental factors supporting the survival of pollinator insects.